Care Preferences Among Chinese Older Adults with Daily Care Needs: Individual and Community Factors. (March 2021) - Lu, Jiehua; Zhang, Li; Zhang, Kunyu
Traditionally, Chinese families have been the primary provider of care for older adults, and older people expected family care. However, along with the modernization and demographic transition, family functions have been weakened, and state-based care has begun to play an essential role in supporting family care for older people. This paper aims to assess the care preferences of older people and the different responsibilities of individuals and communities in modern China. Using data from the 2014 China Longitudinal Aging Social Survey (CLASS) and multinomial logistic regression modeling, we find that family care remains the cornerstone for older adults and their care preferences are associated with individual and community factors, mainly including the number of children, education level, residential area, the presence of health infrastructure and care facilities, and the values associated with filial piety of older adults.